Diversity, distribution, and population structure of Escherichia coli in the lower gastrointestinal tract of humans - Rasel Barua; Paul Pavli; David Gordon; Claire O’Brien (PLoS ONE, 2025)
Several studies report the diversity, and population structure of Escherichia coli (E. coli) in the human gut, but most used faecal specimens as the source of E. coli for analysis. In the present study, we collected mucosal biopsies from three different locations: the terminal ileum, transverse colon, and rectum from 46 individuals. To identify unique strains, we fingerprinted about 3300 isolates of E. coli via the multiple-locus variable-number tandem-repeat analysis (MLVA) technique. An example of each strain per individual then underwent PCR for phylogrouping, and specific phylogrouped strains were further screened to determine whether they belonged to one of four common human-associated sequence types (ST69, ST73, ST95, and ST131), and to identify B2-subtypes. We detected on average 2.5 unique strains per individual. The frequency of unique strain(s) appeared in individuals as follows: 35% (16/46) had only one strain, 22% (10/46) had two strains, 24% (11/46) had three strains and 4% (2/46), 9% (4/46) and 7% (3/46) had 4, 5 and 6 strains, respectively. Strain richness did not depend on gender, age, or disease status. The most abundant phylogroup in all gut locations was B2 followed by A, B1, and D. Strain richness overall and across gut locations was decreased if an individual’s dominant strain belonged to phylogroup B2. ST95, ST131, and ST73 constituted more than half of the total B2 strains. Analysis of B2 sub-types revealed that sub-types IX (STc95) and I (STc131) were more common than other sub-types. The phylogroup and ST of strains at different gut locations did not vary significantly. However, there were multiple examples of individuals who carried strains detected only in one gut location. The present study suggests that particular phylogroups and STs are likely to dominate in different locations in the lower gut of humans.